DNA-Binding Activity of Adeno-Associated Virus Rep Is Required for Inverted Terminal Repeat-Dependent Complex Formation with Herpes Simplex Virus ICP8 - Alex, Martin (American Society for Microbiology, 2012)
Herpes simplex virus (HSV) helper functions for (AAV) replication comprise HSV ICP8 and helicase-primase UL5/UL52/UL8. Here we show that N-terminal amino acids of AAV Rep78 that contact the Rep-binding site within the AAV inverted terminal repeat (ITR) are required for ternary-complex formation with infected-cell protein 8 (ICP8) on AAV single-strand DNA (ssDNA) in vitro and for colocalization in nuclear replication domains in vivo. Our data suggest that HSV-dependent AAV replication is initiated by Rep contacting the AAV ITR and by cooperative binding of ICP8 on AAV ssDNA.